Proceedings of the stock identification workshop, November 5-7, 1985, Panama City Beach, Florida. - Kumpf, H.E., Vaught, R.N., Grimes, C.B., Johnson, A.G., Nakamura, E.L. (eds.) (U.S. Department of Commerce, 1987)
NOAA Technical Memorandum NMFS-SEFC-199